THE DYNAMICS OF BATIK ARTS AT KAMPOENG BATIK LAWEYAN OF SURAKARTA - Edi Kurniadi; Sarwono Sarwono; Felix Ari Dartono (Proceeding of International Conference on Art, Language, and Culture, 2017)
Laweyan sub-district of Laweyan district in the city of Surakarta has been popularly known as the center of batik industry, which has experienced a glorious period as it did in the early 20th century and also experienced a downturn from the 1980s until the 1990s. In its downturn, there were even many appearing young craftsmans who are ductile pioneering batik making business and was able to survive until now (2017). Thus, the batik industries at Laweyan have been secured from extinction. In 2004 Laweyan Village area was officially used as a tourism destination named Kampoeng Batik Laweyan along with the goals to revive the glory of Laweyan batik.The main problem in this research is the survival ability of batik making business in Kampoeng Batik Laweyan, having seen from the dynamics aspect of the decoration which is shown on the fabric processed through the process of making batik. This research is exhibit from the aesthetic, economic, and consistently to upright the approach of historical aspect. The qualitative research used direct observation techniques and in-depth interviews to obtain information from relevant informants.This research concludes that: 1) The Laweyan craftsman are able to produce art of batik handicrafts dynamically and competitively with a variety of ornaments; 2) Every batik company has always presented superior product in the form of batik along with the ornament of special character distinguishing them from other company. In every batik company has always pursue the excellence of both quality and quantity of the products, 4) Begining from 2004 Laweyan Urban Village became a tourist destination under the name of Kampoeng Batik Laweyan, the artisans began to adapt and make batik with a more dynamic decoration, such as souvenirs for tourists.